Ancestral morphology and taxonomic utility of squid statoliths (Cephalopoda: Loliginidae). (24th February 2022) - Díaz-Santana-Iturrios, Mariana; Pacheco-Ovando, Renata; Ibáñez, Christian M; García-Rodríguez, Francisco Javier; Salinas-Zavala, César Augusto; Granados-Amores, Jasmín
ABSTRACT: Loliginid squids from the northeastern Pacific are partially sympatric, and their identification is difficult as their diagnostic characters often overlap. Statoliths are hard structures that may vary with respect to phylogeny and thus have potential use in taxonomy. This, however, has to be investigated using robust methods. Here, we employ geometric morphometrics to evaluate the taxonomic utility of statolith shape in loliginids caught in Mexican waters and to acquire knowledge on statolith evolution through comparative phylogenetic methods. The loliginid species we examined showed specific statolith morphology that facilitates species identification. Our results also show that statolith shape has a strong phylogenetic signal and is a powerful character for species recognition. The ancestral statolith morphologies are not very different from extant forms, probably reflecting the relatively recent origin of the two genera evaluated and their low evolutionary rate. In addition, the evolution of statolith shape in species of the genus Lolliguncula seems to have been faster than that in the genus Doryteuthis, especially in L. panamensis, which could be related to habitat differentiation in the neritic coastal environment inhabited by loliginid squids. Our analysis of statolith shape demonstrates the potential for combining neontology and paleontology in understanding the diversification of loliginid squids.